Some considerations in using the small punch testing for thermally sprayed CoNiCrAlY coatings - Chen, H.; Rushworth, Adam; Sun, Wei; He, J.; Guo, H. (Elsevier, 2018)
Small punch testing exhibits great potential in mechanical characterisation of thin coatings. This testing method can be used to determine the mechanical performance of thermally sprayed coatings, especially to qualitatively characterise the effects of coating defects on the mechanical behaviour. In this work, some considerations in using the small punch testing for coatings are presented through a microstructure evolution analysis of a vacuum plasma sprayed CoNiCrAlY coating under small punch test. The CoNiCrAlY coating was characterised with a large number of un-melted particles as the coating defects. It is shown that the clamping in the small punch test rig can result in micro-cracking around the un-melted particles in the coating prior to testing. It is also found that the un-melted particles in the coating act as predominant cracking sites and fast failure occurred around the unmelted particles. Careful considerations need to be taken into account when using the small punch test for coatings to avoid any changes in the coating microstructure and plasticity during the clamping stage.